Environmental problems in the himalaya - Negi, Sharad Singh (Dehradun, 1982)
This monograph embodies the results of researches carried out on the detiorating Himalayan environment. It deals with problems like slope failure, biotic pressure on forests, shifting cultivation, wildlife, tourism, noise and air pollution, failure of road and canal embankments/retaining walls, visual pollution etc. Over thirty photographe, twenty five tables and numerous figures have been incorporated in the text.
Keywords: Enviormental Protection